Optimizing Milk Run and Use of Bin-Packing in Waste Collection Problems - Prasad, S.; V. Kureethara, J. (International Journal of Engineering and Technology, 2018)
This paper uses the concepts of milk runs as well as bin packing in order to optimize collection and reduce cost. Using the concept of â€œmilk runâ€ and an approach of time minimization, we can optimize the number of trucks and other vehicles used for picking and transporting waste. The objective function involves cost of transportation and is linked to distance travelled to dispose wastes. The constraints are those of vehicle capacity. The profile of different types of trucks obtained from milk run is used to compute number of trucks as well as to allot them to different trips.Â Â